PROFESSIONAL TRAINING OF FUTURE TEACHERS AND ANALYSIS OF CURRENT PROBLEMS IN THE EDUCATION SYSTEM OF UZBEKISTAN (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Training future teachers is one of the central directions of educational reforms today. Within the framework of the educational policy pursued in the Republic of Uzbekistan, the formation of a modern teacher personality, improving the quality of education, and training competitive personnel are set as priority tasks. However, it cannot be denied that the systemic problems that remain in the higher pedagogical education system are a serious obstacle to preparing future teachers for modern professional activities.